2020
DOI: 10.1080/10826084.2020.1791184
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Disorder and COVID-19: Biological Plausibility for Worsened Outcomes

Abstract: Background: Alarms have been raised that COVID-19 may disproportionately affect certain populations with substance use disorders, particularly Opioid Use Disorder (OUD), however warnings have largely focused on social risks such as reduced availability of services. Objectives: This commentary highlights three plausible biological mechanisms for potentially worsened outcomes in patients with OUD who contract COVID-19. Results: Opioid-related respiratory depression may amplify risks of hypoxemia from COVID-19 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 13 publications
0
63
0
1
Order By: Relevance
“…In case of infection, physician should be aware that patients with comorbid COVID-19 and OUD present specificities, including drug interactions between methadone and other medications such as hydroxychloroquine or antiviral agents. Recently, three plausible biological mechanisms for potentially worsened outcomes were suggested ( Schimmel and Manini, 2020 ): opioid-related respiratory depression (amplify risks of hypoxemia), complex opioid immune modulation (may impact host response to the virus), and finally drug-drug interactions, particularly due to cardiac adverse effects. Based on pre-clinical studies, Coppola et al recently suggested an efficacy of hesperidin (antiretroviral drug with an affinity for opioid receptor), but it remains to be tested ( Coppola and Mondola, 2020 ).…”
Section: Results and Observationsmentioning
confidence: 99%
“…In case of infection, physician should be aware that patients with comorbid COVID-19 and OUD present specificities, including drug interactions between methadone and other medications such as hydroxychloroquine or antiviral agents. Recently, three plausible biological mechanisms for potentially worsened outcomes were suggested ( Schimmel and Manini, 2020 ): opioid-related respiratory depression (amplify risks of hypoxemia), complex opioid immune modulation (may impact host response to the virus), and finally drug-drug interactions, particularly due to cardiac adverse effects. Based on pre-clinical studies, Coppola et al recently suggested an efficacy of hesperidin (antiretroviral drug with an affinity for opioid receptor), but it remains to be tested ( Coppola and Mondola, 2020 ).…”
Section: Results and Observationsmentioning
confidence: 99%
“…Consequently, as of March 13, 2020, our methadone clinic increased the number of take-home doses per patient on a case-by-case basis after a thorough risk/benefit assessment. During the COVID-19 outbreak, we incorporated and emphasized new factors in such risk/benefit analysis: i) the increased syndemic vulnerability to SARS-CoV-2 transmission among people who inject drugs ( Vasylyeva et al, 2020 ); ii) the potentially worsened outcomes in patients with opioid use disorder who contract COVID-19 ( Schimmel & Manini, 2020 ); and iii) the facilitation of MMT patients' adherence to lockdown restrictions and social distancing measures.…”
mentioning
confidence: 99%
“…Due to the implementation of SARS-CoV-2 policies and precautions, especially social distancing, patients with SUD are at an increased vulnerability to adverse outcomes related to substance use (Douglas, et al 2020). Increased isolation worsens comorbid mental health disorders and symptoms, increasing the risk of use and overdose (Schimmel, et al 2020). Further, social isolation creates an environment in which people are more likely to use alone, without a partner monitoring them.…”
Section: Discussionmentioning
confidence: 99%